The unexpected reason firms should institute policies to remove email signatures: Quantifying human mortality costs of email signature-based reputation signaling - Joshua M. Pearce (Sustainable Futures)
It has become fashionable in some corporate and academic circles to reputation signal by amending pronouns and/or land acknowledgements to email signatures. Extra information exchange, however, has environmental and social impacts including human mortality from climate destabilization. To illustrate the human mortality cost of carbon-emitting information technology the 1000-ton rule can be used to quantify the cost in human lives. In this study the two types of additional information used in reputation signaling for i) pronouns and ii) land acknowledgments are analyzed by the 1000-ton rule for a case study of Canada. The results of the carbon emission induced human mortality from adding only 3 words in emails to identify gender in a relatively small nations like Canada (∼40 million people) with only a small fraction adding pronouns (∼15 %) are still responsible for prematurely killing a person per year. Likewise, if Canadians all used land acknowledgements in their emails roughly 30 people would be sacrificed annually to reputation signaling. Based on the results of this study the environmental harm and human mortality caused by current information technology infrastructure is such that adding even a few words to an email signature represents an ethically and morally unacceptable human sacrifice. As most of the content of signatures is redundant (far more so than reputation signaling), polices are recommended that signatures are replaced with a hyperlinked name to vital information. To increase efficiency of digital information transfer further policies could eliminate most signatures entirely as emails already identify senders in the header.